Minat Pemuda Tani Pada Usahatani Sayuran Semusim di Kecamatan Cipaku Kabupaten Ciamis, Jawa Barat - Rosliana, Eka; Sulistyowati, Dwiwanti; Pradiana, Wida (Jurnal Penyuluhan Pertanian, 2020)
Qualified human resources and commitment in creating a quality agricultural sector is one of thesuccess factors of sustainable agricultural development. But the current agricultural condition faces a serious problem, the number of young farmers is decreasing. This condition applies in Ciamis regency where the agricultural sector is still the driver of the economic wheel, so the influence on the rate of economic growth is very significant, especially in Cipaku District which has an area of 6,569 ha of agricultural land consisting of dry land and rice fields. However, the interest of the younger generation / youth to cultivate the land is very small, this is due to the perception of farming activities and the fate of farmers are very bleak. In addition, the population working in the agricultural sector is very limited both the main actors and businesses. Especially for the horticultural sector, the role of the main actors was 1,098 (11.7%) and businesses only 164 people (1.7%). This condition has an impact on the sustainability of farming in cipaku subdistrict, because it is actually very dependent on the interest of its youth to continue their parents' profession. The purpose of this research is to describe the interests of farmers, analyze related factors and strategies to increase the interest of farm youth. The analysis used Rank Spearmen and Kendall's W. Analysis shows that the interest of youth farmers in vegetable farming season is relatively high, as well as factors related to the source of information, counseling activities and government support so the interest of farm youth can be improved by carrying out counseling activities as needed